Pengaruh Kecerdasan Spiritual dan Dukungan Sosial terhadap Resiliensi melalui Self Efficacy pada Santri Pondok Pesantren - Diza Hadaita; Mulya Virgonita Iswindari Winta; Erwin Erlangga (SENTRI: Jurnal Riset Ilmiah, 2026)
This research aims to analyze the influence of spiritual intelligence and social support on resilience through self-efficacy in Islamic boarding school students. The subjects of this research werw 100 students consisting of 48 male and 52 female in the city of Pekalongan. The sampling technique used in this research was purposive sampling. Data collection uses a scale consisting of a scale of resilience, spiritual intelligence, social support, and self efficacy. Data analysis uses the Structural Equation Model (SEM) program with SmartPLS. The results of the research show that there is a positive and significant influence between spiritual intelligence on resilience, there is a positive and significant influence between social support on resilience, there is a positive and significant influence between self-efficacy on resilience, there is a positive and significant influence between spiritual intelligence on resiience through sef-efficacy, there is a positive and significant influence between social support on resilience through self-efficacy.